Pollution analysis and quality assessment of heavy metals in the Batanghari River Water, Jambi, Indonesia - Badariah, Badariah; Heraningsih, Sarah Fiebrina; Rainiyati, Rainiyati; Yulistian, Saldi; Jauza, Zia (Brawijaya University, 2026)
The Batanghari River is currently under serious threat due to extensive anthropogenic activities, including illegal gold mining, domestic waste discharge, and industrial effluents. This study aimed to evaluate the biogeochemical characteristics and the extent of heavy metal contamination in the Batanghari River water. Pollution indices, including the Single Factor Pollution Index (Pi), Nemerow Pollution Index (NPI), Contamination Factor (CF), Degree of Contamination (Cd), Pollution Load Index (PLI), and Potential Ecological Risk Index (PERI), were calculated to assess contamination levels and ecological risk. The results showed that the Batanghari River is heavily contaminated with heavy metals, with NPI values ranging from 4.05 to 35.8, exceeding the threshold for severe pollution (NPI>3.0). Mercury (Hg) was identified as the dominant pollutant, followed by cadmium (Cd), copper (Cu), and lead (Pb). The high Hg concentration is associated with illegal gold mining activities along the riverbanks. The computed PLI values (2.7-5.1) and Cd values (>24) confirmed deterioration in the river water quality. PERI analysis revealed very high ecological risk at several sites, with values up to 1,298, mainly attributed to Hg and Cd toxicity. Without proper treatment, the Batanghari River is no longer suitable for direct use, posing significant ecological and human health risks. Without proper treatment, the Batanghari River is no longer suitable for direct use, posing significant ecological and human health risks.